Effect of surface treatments on fracture resistance of root filled teeth with bonded fibre posts. Issue 4 (21st November 2013) - Feiz, Atiyeh; Samimi, Pooran; Karami, Ali; Badrian, Hamid; Goroohi, Hossein; Swift, Edward J.
Abstract Background/Aim This study examined the effect of several dentin surface treatments on fracture resistance of root filled teeth containing bonded fibre posts. Material and methods The roots of 84 single‐canal premolars were instrumented, filled with gutta‐percha and randomly divided into seven groups. The coronal 9 mm of gutta‐percha was removed to create a post space. In the experimental groups, canals were irrigated with distilled water, 37% phosphoric acid, 5% sodium hypochlorite, 17% EDTA, 5% sodium hypochlorite followed by 17% EDTA or 5% sodium hypochlorite followed by 10% ascorbic acid. Fibre posts were cemented using Panavia F2.0 resin cement, and the specimens were mounted in acrylic resin blocks. Following 1‐week storage in an incubator, specimens were thermocycled and their fracture resistance was determined using a universal testing machine. Data were analysed using the Kruskal–Wallis test. Results Mean fracture resistance values ranged from 465.8 N in specimens treated with sodium hypochlorite and ascorbic acid to 739.1 N for those treated with sodium hypochlorite only. However, differences in fracture resistance were not statistically significant (P = 0.114). Conclusions None of the surface treatments improved vertical fracture resistance of root filled teeth containing bonded fibre posts.